Effect Of Cooking Methods And Conditions On Heterocyclic Amines Content In Satay And Roasted Marinated Chicken - Mohd Mukhtar, Mohd Safzan (2009)

(untitled)
The objectives of this study were to determine the effect of cooking method on HAs concentration of chicken and beef satay and the effect of marinating and different cooking conditions on HAs concentration of roasted chicken. Six common HAs were investigated: 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), 2- amino 3,4-dimethylimidazo[4,5-f]quinoline (MeIQ), 2-amino-3,8-dimethylimidazo[ 4,5-f]quinoxaline (MeIQx), 2-amino-3,4,8-trimethylimidazo[4,5- f]quinoxaline (4,8-DiMeIQx), 2-amino-3,7,8-trimethylimidazo[4,5-f]quinoxaline (7,8-DiMeIQx), 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP). Samples were extracted using 1M NaOH and ethyl acetate and clean up on solid phase extraction (SPE) column. The samples were then analysed using high performance liquid chromatography (HPLC) equipped with photodiode-array detector (DAD). Chicken and beef satay were grilled to two different degrees of doneness (medium and well done). Three types of cooking method were applied UPLOAD to both types of satay i.e. charcoal grilled (treatment A), microwave pretreatment prior to grilling (treatment B), and deep fried-microwave (treatment C). Both chicken and beef satay samples which undergone microwave pretreatment prior to grilling (treatment B) showed significantly (p<0.05) lower HAs concentration as compared to charcoal grilled satay (treatment A). Deep fried-microwave (treatment C) was applied to both types of satay as an alternative method to cook satay and was proven to produce lesser HAs as compared to treatments A and B in medium and well done cooked satay. HAs concentration were compared in marinated and unmarinated chicken before roasting. Three roasting conditions were applied to chicken i.e. 160°C for 120 min (treatment X), 180°C for 90 min (treatment Y) and 200°C for 60 min (treatment Z). The study showed that marinated chicken produced significantly (p<0.05) lower HAs concentration as compared to unmarinated chicken in all three different cooking treatments. Meanwhile, roasting at 160°C for 120 min (treatment X) was found to produce the lowest HAs as compared to the other two treatments, 180°C for 90 min (treatment Y) and 200°C for 60 min (treatment Z). Marinating the roasted chicken with percik sauce has been shown to produce the lowest HAs concentration when the samples were exposed to 200°C for 60 min (treatment Z) as compared to other marinating sauces used in this study. These results revealed that marinating chicken before roasting with various spices and herbs which contain rich amount of antioxidants may reduce significantly the formation of mutagenic / carcinogenic HAs in the products.